SETD4 Confers Cancer Stem Cell Chemoresistance in Nonsmall Cell Lung Cancer Patients via the Epigenetic Regulation of Cellular Quiescence - Yuehong Wang; Yuman Yu; Weijun Yang; Linying Wu; Yaoshun Yang; Qianyun Lu; Jianying Zhou (Hindawi Limited, 2023)
Increasing evidence indicates that quiescent cancer stem cells (CSCs) are a root cause of chemoresistance. SET domain-containing protein 4 (SETD4) epigenetically regulates cell quiescence in breast cancer stem cells (BCSCs), and SETD4-positive BCSCs are chemoradioresistant. However, the role of SETD4 in chemoresistance, tumor progression, and prognosis in nonsmall cell lung cancer (NSCLC) patients is unclear. Here, SETD4-positive cells were identified as quiescent lung cancer stem cells (qLCSCs) since they expressed high levels of ALDH1 and CD133 and low levels of Ki67. SETD4 expression was significantly higher in advanced-stage NSCLC tissues than in early-stage NSCLC tissues and significantly higher in samples from the chemoresistant group than in those from the chemosensitive group. Patients with high SETD4 expression had shorter progression-free survival (PFS) times than those with low SETD4 expression. SETD4 facilitated heterochromatin formation via H4K20me3, thereby leading to cell quiescence. RNA-seq analysis showed upregulation of genes involved in cell proliferation, glucose metabolism, and PI3K-AKT signaling in activated qLCSCs (A-qLCSCs) compared with qLCSCs. In addition, SETD4 overexpression facilitated PTEN-mediated inhibition of the PI3K-mTOR pathway. In summary, SETD4 confers chemoresistance, tumor progression, and a poor prognosis by regulating CSCs in NSCLC patients.